In Silico Investigation of 2-Anilino 4-Amino Substituted Quinazolines as Potential Inhibitors of Plasmodium falciparum Dihydroorotate Dehydrogenase - Aurellyallodia Faiza Kusuma; Muhammad Farhan Shadiq; Rizarullah; Reza Aditama; Trina Tallei; Masduki, Fifi Fitriyah (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2025)
Malaria continues to present significant global health challenges due to emerging resistance against conventional antimalarial drugs, necessitating novel therapeutic agents targeting Plasmodium falciparum. Dihydroorotate dehydrogenase (DHODH) is a crucial target in antimalarial drug development due to its essential role in pyrimidine biosynthesis within Plasmodium species. This study aimed to evaluate several candidate compounds from previous study - namely ligand 56, 65, 89 and 90 - as potential DHODH inhibitors using in silico methods, including molecular docking and molecular dynamics (MD) simulations. Molecular docking was performed using AutoDock Vina against the DHODH receptor structure (PDB ID: 4CQ8). The results indicated that ligand 89 exhibited the highest binding affinity (-9.575 kcal/mol), followed by ligands 90, 56, and 65, all demonstrating superior affinity compared to the control compound chloroquine (-7.462 kcal/mol). Interaction analyses revealed the formation of hydrogen bonds with key residues HIS185, GLY181, and ARG265, along with significant pi-sulfur interactions involving residue CYS184, thereby stabilizing the ligand interactions within the DHODH active site. Pharmacokinetic evaluations conducted using SwissADME revealed that all candidate ligands met Lipinski's rule and demonstrated high gastrointestinal absorption, despite their generally low solubility. MD simulations conducted over 100 ns at 300 K showed that all ligand-DHODH complexes, maintained stability, with Root Mean Square Deviation (RMSD) values ranging between 1.0 and 3.5 Å throughout the simulation. Overall, the findings suggest that ligand 89 and other evaluated ligands hold significant potential for further development as DHODH inhibitors in the pursuit of novel antimalarial drug candidates.